2002
DOI: 10.1093/molehr/8.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mifepristone and levonorgestrel on expression of steroid receptors in the human Fallopian tube

Abstract: It is likely that mifepristone or levonorgestrel in the future will find extended use for contraceptive purposes. It is therefore essential to characterize the modes of action of these compounds. To assess the effect on the human Fallopian tube, 24 women with regular menstrual cycles and proven fertility, admitted to the hospital for voluntary sterilization by laparoscopic technique, were randomly allocated to a control or one of two treatment groups. Treatments were given with either a single dose of 200 mg m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 20 publications
0
18
0
5
Order By: Relevance
“…To determine the response to gonadotropins and induction of ovulation (62), immature female mice (30 mice in one experiment) were given a single injection of 5 IU eCG or saline (hormone vehicle). eCG was administered intraperitoneally for 24 or 48 h. In addition, some of the animals (40 mice in one experiment) were injected intraperitoneally with 5 IU eCG followed 48 h later with a single injection of 5 IU hCG (ip) for the indicated time (6,12,24, and 48 h). The fallopian tubes and uteri were grossly dissected free of contaminating tissue (e.g., adipose tissue) after mice were killed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the response to gonadotropins and induction of ovulation (62), immature female mice (30 mice in one experiment) were given a single injection of 5 IU eCG or saline (hormone vehicle). eCG was administered intraperitoneally for 24 or 48 h. In addition, some of the animals (40 mice in one experiment) were injected intraperitoneally with 5 IU eCG followed 48 h later with a single injection of 5 IU hCG (ip) for the indicated time (6,12,24, and 48 h). The fallopian tubes and uteri were grossly dissected free of contaminating tissue (e.g., adipose tissue) after mice were killed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…Relative to ovary and uterus, earlier studies have demonstrated that specific binding sites for P 4 can be observed using the ligand-binding characteristic assay in human and rodent fallopian tubes, (37,45,52,53,73). Later reports have demonstrated that PR mRNA and protein expression can be detected by RT-PCR (6,50,66), Western blot analysis (6,66), and immunohistochemical localization (1,6,18,19,50,66). Although PR proteins display cyclic changes in human fallopian tubes during the menstrual cycle (1,73), PR protein isoforms expressed in the fallopian tubes, their regulation, and their role in tubular function are much less well understood.…”
mentioning
confidence: 99%
“…De estos 22 artículos, publicados entre 1995 y el 2010, diez estuvieron diseñados para medir el efecto sobre la ovulación (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) , doce el efecto sobre el endometrio (9,12,13,(18)(19)(20)(21)(22)(23)(24)(25)(26) y tres el efecto sobre los espermatozoides (27)(28)(29) . De estos estudios, nueve correspondían a ensayos clínicos (8,9,14,15,18,19,23,24,27) , ocho a estudios cuasi-experimentales (10)(11)(12)(13)16,25,26,29) , tres a estudios observacionales (17,22,28) y dos a estudios in vitro (20,21) .…”
Section: Artículos Seleccionados Para El Análisisunclassified
“…De estos estudios, nueve correspondían a ensayos clínicos (8,9,14,15,18,19,23,24,27) , ocho a estudios cuasi-experimentales (10)(11)(12)(13)16,25,26,29) , tres a estudios observacionales (17,22,28) y dos a estudios in vitro (20,21) . Tres estudios fueron hechos en animales (los tres correspondientes a diseños cuasiexperimentales (13,16,25) ) y el resto en humanos.…”
Section: Artículos Seleccionados Para El Análisisunclassified
See 1 more Smart Citation